Meta Analysis and Agricultural Applications - Küçükönder, Hande; Efe, Ercan; Küçükönder, Hande (Kahramanmaras Sutcu Imam Univ, 2014)
In this study, meta-analysis, which is used in order to gather published or unpublished studies on a specific topic conducted by the researchers, is introduced and is intended to guide to investigators who will study on this issue. In the research, 8 different application samples are chosen, and the data of these samples analyzed in statistical software package Comprehensive Meta-Analysis by transferring to MSQL database. During the studies, odds ratio is selected as measure of impact and unification of studies is performed in two ways according to Mantel-Haenszel and Peto methods.. Meta-analysis summary odds ratios for practices based on the assumption that both models support each other in all samples examined and was found (p < 0.05).
Keywords: Meta-Analysis; Odss Ratio; Mantel-Haenszel; Peto